"Hit-and-run" effects of paramyxoviruses as a basis for chronic respiratory disease - Holtzman, Michael J; Shornick, Laurie P; Grayson, Mitchell H; Kim, Edy Y; Tyner, Jeffrey W; Patel, Anand C; Agapov, Eugene; Zhang, Yong (The Pediatric infectious disease journal, 2004)
The traditional scheme for asthma pathogenesis depends on increased T helper type 2 (Th2) over T helper type 1 (Th1) responses to allergic and nonallergic stimuli and consequent airway inflammation, hyperreactivity and hypersecretion. Here we question whether the innate immune system, including airway epithelial cells, and the adaptive one may manifest an aberrant antiviral response as an additional basis for chronic inflammatory diseases, including asthma. We focused on the signal transduction and genetic basis for mucosal immunity, inflammation and remodeling, especially in relation to airway diseases. We concentrated on the response to paramyxoviruses because these agents are closely associated with common acute and chronic airway diseases. We used viral, cellular and mouse models, as well as human subjects, for study and made comparisons among these systems. Our approach aims to answer 2 major questions: (1) what are the factors that control acute paramyxoviral infection; and (2) how can these transient infections cause long term airway disease? Our studies show that antiviral defense depends on a special network of epithelial immune response genes that signal to the adaptive immune system. Viruses ordinarily trigger this network, but it is also permanently activated in asthma, even in the absence of viral infection. In addition, we find that, in susceptible genetic backgrounds, respiratory viruses cause a "hit-and-run" phenomenon indicated by the development of an asthmatic phenotype long after the infection has cleared. On the basis of this information, we developed a new scheme for asthma pathogenesis that includes epithelial, viral and allergic components and allows viral reprogramming of host behavior.